(untitled) (Modern education and development, 2025)
The stability of a national currency is one of the key indicators of a country’s economic resilience and financial security. This article provides a systematic analysis of the foreign trade balance and its impact on the value of the national currency. The study examines the volumes of exports and imports, the positive or negative trends in the trade balance, and their mechanisms of influence on exchange rate stability. Through an analytical approach, the paper highlights in detail how factors such as global price fluctuations, the flow of foreign exchange revenues, and changes in import volumes affect the national currency exchange rate. The analysis, based on the case of Uzbekistan, demonstrates that balancing the foreign trade balance, strengthening export diversification, and reducing import dependency are of strategic importance in ensuring the stability of the national currency. The practical significance of this research lies in its scientifically grounded recommendations aimed at optimizing government policy, effectively directing foreign trade policy, and reducing the risks of exchange rate instability.